Cyclin D1 overexpression in Algerian breast cancer women: correlation with CCND1 amplification and clinicopathological parameters - Mohammedi, Latifa (Afr Health Sci, 2019)
BACKGROUND: Cyclin D1 which is associated with cell cycle regulation is solidly established as an oncogene with an important pathogenetic role in breast carcinomas. OBJECTIVES: The aim of this study was to relate the Cyclin D1 protein overexpression with the amplification of its gene CCND1 in Estrogen Receptors (ER) positive breast carcinomas, in order to investigate the prognostic effect of their aberrations in relation to ER status, also to correlate the Cyclin D1 overexpression with other prognostic parameters. MATERIALS AND METHODS: Chromogenic in situ hybridization (CISH) was used to identify CCND1 amplification on formalin-fixed paraffin-embedded invasive ductal carcinoma, in which immunohistochemistry (IHC) had previously been performed in order to evaluate the pathological relevance of Cyclin D1 overexpression in human breast cancer (n = 138). RESULTS: CCND1 amplification was identified in 17/138 (12.3%) tumors and 78/138 (56.5%) tumors have overexpressed Cyclin D1. A significant correlation was identified between CCND1 amplification and Cyclin D1 overexpression (P < 0.001) and both Cyclin D1 and CCND1 were related with ER expression. CONCLUSION: Our results show a significant correlation between Cyclin D1 overexpression and CCND1 amplification. Overexpression of Cyclin D1was observed in high proportion of breast cancer which should be considered for routine diagnosis.